Autophagy Receptor Tollip Facilitates Bacterial Autophagy by Recruiting Galectin-7 in Response to Group A Streptococcus Infection - Lin, Ching-Yu; Nozawa, Takashi; Minowa-Nozawa, Atsuko; Toh, Hirotaka; Hikichi, Miyako; Iibushi, Junpei; Nakagawa, Ichiro (Frontiers in Cellular and Infection Microbiology, 2020)
Bacterial autophagy—a type of macroautophagy that is also called xenophagy—selectively targets intracellular bacteria such as Group A Streptococcus (GAS), a ubiquitous pathogen responsible for numerous serious diseases, including pharyngitis, skin infections, and invasive life-threatening infections. Although bacterial autophagy is known to eliminate invading bacteria through the action of autophagy receptors, the underlying mechanism remains incompletely elucidated. Here, we revealed that Tollip also functions as a bacterial-autophagy receptor and is involved in the intracellular immunity that defends against bacterial infection. Tollip was recruited to GAS-containing endosomal vacuoles before the escape of GAS into the cytosol, and knockout of Tollip disrupted the recruitment of other autophagy receptors, such as NBR1, TAX1BP1, and NDP52, to GAS-containing autophagosomes and led to increased intracellular survival of GAS. Furthermore, Tollip was found to be required for the recruitment of galectin-1 and -7 to GAS-containing autophagosomes, and immunoprecipitation results indicated that Tollip interacts with galectin-7. Lastly, our data also revealed that galectin-1 and -7 are involved in the restriction of GAS replication in cells. These results demonstrated that Tollip functions in bacterial autophagy by recruiting other autophagy receptors and galectins.